Educational Empowerment Through Technological Integration: A Pathway To Enhancing Learning Outcomes in Islamic Studies - Dian Dian; Ishma Shafiyatu Sa’diyah; Siti Fatmawati; Winda Nurmaulida S (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
One of the Islamic boarding schools that has long carried out this noble mission is Pondok Daarul Amien Gontor 10. As an Islamic educational institution that has been established for a long time, Pondok Daarul Amien Gontor 10 is not only a place of education, but also a center for developing Islamic character and personality. The purpose of this study is to analyze teacher performance in evaluating the role and contribution of Islamic education in pondok daarul amien gontor 10. This research method uses This research is designed as a qualitative field research with the main focus on analyzing teacher performance in Pondok Daarul Amien Gontor 10. The purpose of this study is to gain an in-depth understanding of the role and contribution of teachers in the context of Islamic education in the institution. Teacher Performance in Evaluating the Role and Contribution of Islamic Education in Pondok Daarul Amien Gontor 10 provides an in-depth understanding of the role of teachers in shaping learners holistically. Teachers in this institution not only act as teachers, but also as spiritual mentors who guide students in the journey of achieving religious knowledge and building Islamic character. The research findings highlight their success in creating a holistic learning environment, where Islamic ethical values, morality, and spirituality are well integrated in the formal curriculum and the daily lives of learners